Optimization of stir-baked technology for Flos Sophorae Immaturus tea according to quadratic regression rotation-orthogonal design method and quality evaluation - Fang Hong, Shang; Long Yun, Li; Xu Hong, Song; Jun, Tan; Ji Rui, Wang; Gang, Chen (Italian Journal of Food Science, 2021)
This study aimed to optimize the stir-baked technology for Flos Sophorae Immaturus tea (FSIT) and evaluate the quality of FSIT. The optimum stir-baked conditions were found to be as follows: amount, 3.9 kg; rotation speed, 400 r/min; and time required to reach the temperature of 120°C, 5 min and maintained for 3.9 min after adding 15 mL of 1% stevioside. The machine-made FSIT soup was clear and golden in color, with charred taste, no bitterness, no peculiar smell, and improved sensory quality under the above-mentioned conditions. Heavy metal contents and microorganisms did not exceed the national standards.